How relevant is social interaction in second language learning? - Verga, Laura; Kotz, Sonja A. (Frontiers in Human Neuroscience, 2013)
Verbal language is the most widespread mode of human communication, and an intrinsically social activity. This claim is strengthen by evidence emerging from different fields, which clearly indicate that social interaction influences human communication, and more specifically, language learning. Indeed, research conducted with infants and children shows that interaction with a caregiver is necessary to acquire language. Further evidence on the influence of sociality on language comes from social and linguistic pathologies, in which deficits in social and linguistic abilities are tightly intertwined, as it is the case for Autism, for example. However, studies on adult second language learning have been mostly focused on individualistic approaches, partly because of methodological constraints especially of imaging methods. The question as to whether social interaction should be considered as a critical factor impacting upon adult language learning still remains underspecified. Here, we review evidence in support of the view that sociality plays a significant role in communication and language learning, in an attempt to emphasize factors that could facilitate this process in adult language learning. We suggest that sociality should be considered as a potentially influential factor in adult language learning and that future studies in this domain should explicitly target this factor.